2003
DOI: 10.1034/j.1600-0609.2003.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trends of hemoglobin levels in a Japanese population – RERF's Adult Health Study subjects

Abstract: Conflicting results have been reported on the long-term relationship between hemoglobin (Hb) level and age. We analyzed that relationship over a 40-yr period in a Japanese population, adjusting for the effects of sex, birth cohort, smoking, and anemia-associated diseases. We used Hb levels measured biennially between 1958 and 1998 for 4858 Adult Health Study subjects of the Radiation Effects Research Foundation. Using the mixed-effects model, we showed that the aging Hb profile varied by sex (P < 0.001) and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 34 publications
4
21
2
1
Order By: Relevance
“…To our knowledge, this study is the first nationally representative cross-sectional study to evaluate the trends in nutritional status of community-dwelling elderly people [6,7,11]. In the current study, similar prevalence of anemia was observed in men (19.3%) and women (21.7%) compared to other developed countries.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…To our knowledge, this study is the first nationally representative cross-sectional study to evaluate the trends in nutritional status of community-dwelling elderly people [6,7,11]. In the current study, similar prevalence of anemia was observed in men (19.3%) and women (21.7%) compared to other developed countries.…”
Section: Discussionsupporting
confidence: 58%
“…In the United States (US), anemia prevalence increases with advancing age after 50 years and rises to more than 20% at age ≥ 85 years [4,5]. In the community dwelling elderly Japanese population, the prevalence of anemia was reported to increase with age [6]. However, this study was not conducted in a nationally representative sample and limited the highest age category to ≤ 80 years.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In line with most cross-sectional studies and the findings of three longitudinal investigations, [24][25][26] hemoglobin concentration decreased and prevalence of anemia increased with increasing age. Annual rates of decline of hemoglobin concentration estimated cross-sectionally and longitudinally were similar and consistent with those reported in longitudinal surveys of 8-and 40-year duration.…”
Section: Associations Of Mild Anemia With Other Clinical Conditionssupporting
confidence: 56%
“…Moreover, decrease in average Hb during 1 year after PPI treatment was 0.38±0.87 g/dl, which was significantly greater than the reported annual decrease in Hb of 0.08-0.04 g/dl/year for men and 0.05-0.04 g/dl/year for women. 13 These findings suggest that PPI decrease Hb. It is possible that PPI were prescribed to the patients with peptic ulcer and that the peptic ulcer itself caused anemia, but patients with major bleeding within 1 year were excluded from the present study and history of peptic ulcer was not associated with low Hb in the present subjects.…”
Section: Discussionmentioning
confidence: 72%